A study to evaluate safety and tolerability of repeated doses of tirasemtiv in patients with amyotrophic lateral sclerosis. Issue 7 (December 2013) - Shefner, Jeremy M.; Watson, Mary Lou; Meng, Lisa; Wolff, Andrew A.; ,
Abstract: Tirasemtiv is a fast skeletal muscle activator that increases the sensitivity of the sarcomere to calcium, increasing the efficiency of muscle contraction when the muscle is stimulated at submaximal contraction frequencies. A previous study showed single doses of tirasemtiv to be well tolerated and associated with potentially important improvements in a variety of functional outcomes. This study determined safety of tirasemtiv when given at doses up to 500 mg daily for three weeks. Tirasemtiv was given as a single daily dose up to 375 mg for two weeks, with and without concomitant riluzole. In a separate cohort, an ascending dose protocol evaluated a total dose of 500 mg daily given in two divided doses. Safety and tolerability were assessed, as well as measures of function, muscle strength and endurance. Results showed that tirasemtiv was well tolerated, with dizziness the most common adverse event. Tirasemtiv approximately doubled the serum concentration of riluzole. Trends were noted for improvement in ALSFRS-R, Maximum Minute Ventilation, and Nasal Inspiratory Pressure. In conclusion, tirasemtiv is well tolerated and can be given safely with a reduced dose of riluzole. Positive trends in multiple exploratory outcome measures support the further study of this agent in ALS.